Determinants of Stock Return: A Comparison of Financial Distress and Non Financial Distress Firms in Manufacturing Company Listed of Indonesia Stock Exchange - Chotimah Chotimah; Wulansari Wulansari (Media Riset Bisnis & Manajemen, 2018)
AbstractPurpose –The purpose of this study is to examine the difference of stock return between financial distress and non-financial distress firms and to examine the influence of financial health, financial leverage, liquidity, profitability, book to market equity and size to stock return on the manufacturing firms listed at Indonesia Stock Exchange in the period 2012-2016.Design/Methodology/Approach- The dependent variable in this study is the stock return (SR), while the independent variable are financial health, financial leverage, liquidity and profitability while the variable control are book to market equity and size. The method used is a non-parametric difference test using mann-whitney U and multi-regression panel data with dummy variable using fixed effect model.Findings - The findings obtained this study indicate that there is difference of stock return between financial distress and non-financial distress company, financial distress and financial leverage has a negative influence to stock return and there is positive influence profitability and size to stock return, while liquidity and book to market equity has no impact on stock return. The firms need to increase the level of financial health and increase corporate profits by reduce the level of corporate debt so it will increase the stock return.